2018
DOI: 10.5152/tjg.2018.17533
|View full text |Cite
|
Sign up to set email alerts
|

Do bad habits bring a double constipation risk?

Abstract: Compared with dietary habits, behavioral aspects surrounding defecation are more related to chronic constipation. Our results indicate that the modification of these bad habits may be the first step in chronic constipation treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In a Spanish study of 414 participants aged over 50 years, physical activity was not associated with constipation [14]. In a another Spanish study of 415 participants aged 43.8 years, exercise habits were not related to constipation [15]. The discrepancies among these study results may be explained, at least in part, by the differences in the definition of constipation, exercise intensity, race, sample size, study design, assessment of exercise, and age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Spanish study of 414 participants aged over 50 years, physical activity was not associated with constipation [14]. In a another Spanish study of 415 participants aged 43.8 years, exercise habits were not related to constipation [15]. The discrepancies among these study results may be explained, at least in part, by the differences in the definition of constipation, exercise intensity, race, sample size, study design, assessment of exercise, and age.…”
Section: Discussionmentioning
confidence: 99%
“…In Icelandic, Swedish, Hong Kong, two Chinese and three Japanese studies showed the inverse association between constipation, functional constipation, and PA [4-11]. On the other hand, In US, British, and two Spanish studies were no association between PA and constipation was found [12-15]. Epidemiological evidence on this issue has been limited and inconsistent.…”
Section: Introductionmentioning
confidence: 99%